Engineering the Lymphatic Network: A Solution to Lymphedema. Issue 6 (27th January 2021) - Jia, Wenkai; Hitchcock‐Szilagyi, Hannah; He, Weilue; Goldman, Jeremy; Zhao, Feng
Abstract: Secondary lymphedema is a life‐long disorder characterized by chronic tissue swelling and inflammation that obstruct interstitial fluid circulation and immune cell trafficking. Regenerating lymphatic vasculatures using various strategies represents a promising treatment for lymphedema. Growth factor injection and gene delivery have been developed to stimulate lymphangiogenesis and augment interstitial fluid resorption. Using bioengineered materials as growth factor delivery vehicles allows for a more precisely targeted lymphangiogenic activation within the injured site. The implantation of prevascularized lymphatic tissue also promotes in situ lymphatic capillary network formation. The engineering of larger scale lymphatic tissues, including lymphatic collecting vessels and lymph nodes constructed by bioengineered scaffolds or decellularized animal tissues, offers alternatives to reconnecting damaged lymphatic vessels and restoring lymph circulation. These approaches provide lymphatic vascular grafting materials to reimpose lymphatic continuity across the site of injury, without creating secondary injuries at donor sites. The present work reviews molecular mechanisms mediating lymphatic system development, approaches to promoting lymphatic network regeneration, and strategies for engineering lymphatic tissues, including lymphatic capillaries, collecting vessels, and nodes. Challenges of advanced translational applications are also discussed. Abstract : Lymphedema is associated with tissue swelling, chronic inflammation, and immune dysfunction that impair patients' quality of life. Regeneration of lymphatic tissues and restoration of lymphatic vessel functions represent a promising and effective treatment for lymphedema. The present work reviews state‐of‐art approaches for engineering lymphatic tissues and challenges in their translational applications.